FOUR ILLUSTRATED NEWS MAGAZINES: A COMPARATIVE STUDY OF CULTURAL INTERACTIONS IN POST‐WAR GERMANY. (12th March 2018) - Knowles, Christopher; Vossen, Julia
ABSTRACT: Newspapers and magazines are cultural products and can therefore be considered as works of fiction as well as fact. This article discusses the creation of the news magazine Der Spiegel as an example of cultural transfer, providing an insight into the diverse origins of Der Spiegel, the influence of the magazine on post‐war German journalism, and the adoption of British and American models by much of the German press. The origins, format, content, and writing style of four magazines published in the US, Britain, and Germany are analysed and compared: the US magazine Time, the British weekly magazine News Review, Diese Woche, the immediate precursor to Der Spiegel, and Heute, an illustrated feature magazine published in the US Zone of Germany. All four magazines used colourful language and stylistic devices to interpret the news as well as report it and sometimes peddled a fiction of objectivity that was in fact highly opinionated. Diese Woche was no different in this respect from Time and News Review . The idea that British and American news reporting was accurate and truthful and never mixed fact and opinion, whereas it was only the German press that mixed information with tendentious comment,  was one of many myths circulated in post‐war Germany.